PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS KINERJA KARYAWAN PADA PERUM DAMRI "“ CABANG PONTIANAK - Putri, Mofit Lestari (Jurnal KIAFE, 2023)
This research was conducted to determine the effectiveness of employee performance and the factors that influence the implementation of the accounting information system at Perum DAMRI - Pontianak Branch. Purposive sampling technique was used to obtain a research sample of 40 employees. This research uses simple correlation and regression analysis techniques. The results of the research, namely SIA in the company, show that employee performance is increasing, from the skills aspect, many employees have mastered the accounting information system. The research results also show that the accounting information system greatly influences the effectiveness of employee performance.